2011
DOI: 10.1142/s1793292011002846
|View full text |Cite
|
Sign up to set email alerts
|

A FACILE SYNTHESIS OF SHAPE- AND SIZE-CONTROLLED α-Fe2O3 NANOPARTICLES THROUGH HYDROTHERMAL METHOD

Abstract: O 3 nanoparticles have wide-ranging applications such as in catalysis, sensoring, painting, etc. This is the reason to study their controlled synthesis. Here we have investigated the synthesis of uniform α-Fe 2 O 3 nanoparticles using amino acids as morphology control agents. The products were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravimetry (TG) and differential thermal analysis (DTA). It was found that the type and the amount of amino acids as well as the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Uniform rhombic-shaped Fe 2 O 3 nanoparticles were prepared according to the method described previously. 40,41 In a typical procedure, 2 mmol of FeCl 3 $6H 2 O and 0.5 mmol of lysine were rst dissolved in 100 mL distilled water under vigorous stirring at room temperature for 2 h to form a clear solution. Subsequently, the mixture was transferred to a Teon-lined stainless steel autoclave of 150 mL capacity, sealed, and maintained at 120 C for 14 h. Aerwards, the autoclave was allowed to cool down to room temperature.…”
Section: Synthesis Of Fe 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…Uniform rhombic-shaped Fe 2 O 3 nanoparticles were prepared according to the method described previously. 40,41 In a typical procedure, 2 mmol of FeCl 3 $6H 2 O and 0.5 mmol of lysine were rst dissolved in 100 mL distilled water under vigorous stirring at room temperature for 2 h to form a clear solution. Subsequently, the mixture was transferred to a Teon-lined stainless steel autoclave of 150 mL capacity, sealed, and maintained at 120 C for 14 h. Aerwards, the autoclave was allowed to cool down to room temperature.…”
Section: Synthesis Of Fe 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…According to Durmus et al (2009), insulating magnetite with Lys increased activation energy. Kandori et al (2006) and Wang et al (2009Wang et al ( , 2011 observed that amino acids have an effect on the shape and size of particles of hematite. Kandori et al (2006) obtained spherical hematite particles using L-Phe, L-Ser, L-Ala and ellipsoidal hematite particles using L-Gln and L-Glu.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have investigated the synthesis of iron oxide–hydroxides with amino acids/peptides such as: goethite/Cys (Cornell et al 1990), hematite/L-Phe, L-Ser, L-Ala, L-Gln or L-Glu (Kandori et al 2006), ferrihydrite–lepdocrocite/L-His, L-Thr or Cys (Mantion et al 2008), magnetite/L-Lys (Durmus et al 2009), hematite/L-Lys or D-Asn (Wang et al 2009), magnetite/L-carnosine (Durmus et al 2011), hematite/L-Glu or L-Asp or L-Lys or D-Asn (Wang et al 2011). The main goal these experiments were not to investigate prebiotic chemistry, but to synthesize novel catalysts or for use in medical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature or a neutral solution (pH ∼7) favors the formation of hematite, while the low and high pH values (pH <4, and pH >10) are preferred for the growth of goethite. , The structural transformation between various oxides and oxyhydroxides is proposed to be driven either by a dissolution-recrystallization process due to the decrease in solubility or through a topotactic transformation caused by the existence of structural continuity between hematite and ferrihydrite. In many cases, the obtained monodispersed hematite particles are found to be consisting of much smaller subcrystals, where aggregation of these smaller crystallites yields large mesocrystals, mostly with a single-crystal structure. This process was later explained by the oriented attachment mechanism, where adjacent particles can be assembled by sharing a common crystallographic orientation to reduce the total surface energy. This mechanism is thus considered to be a general pathway for the growth of hematite in solution and has been adopted in many publications. …”
Section: Introductionmentioning
confidence: 99%